2009
DOI: 10.4314/eamj.v77i1.46371
|View full text |Cite
|
Sign up to set email alerts
|

Obstructed abdominal hernia at the Wesley Guild Hospital, Nigeria

Abstract: Objective: To determine the incidence, pattern and outcome of obstructed abdominal wall hernia in a semi-urban and rural community. Design: A proforma was drafted to study all consecutive patients operated for obstructed anterior abdominal wall hernia over a period of five years. Clinical findings, preoperative treatment, operative findings and postoperative outcome were documented. Setting: Teaching hospital located in a semi-urban community comprising mostly agrarian population. Patients: A total 110 adult p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 7 publications
1
23
0
Order By: Relevance
“…John T Jenkins et al reported that acute groin surgery had a 7% mortality rate. 28,29 Andrews 22 found a mortality of 37% for complicated groin hernias. McEntee 8 and colleagues recorded an overall mortality of 10.4%.…”
Section: Discussionmentioning
confidence: 99%
“…John T Jenkins et al reported that acute groin surgery had a 7% mortality rate. 28,29 Andrews 22 found a mortality of 37% for complicated groin hernias. McEntee 8 and colleagues recorded an overall mortality of 10.4%.…”
Section: Discussionmentioning
confidence: 99%
“…This subject proves the severity of the inguinal hernia disease in Africa. In the long-term followup period, chronic groin pain and recurrence are the most important issues (32).…”
Section: Surgical Diagnosesmentioning
confidence: 99%
“…Adesunkanmi et al reported the factors that affected the outcomes of inguinal hernia operations in Nigeria (32). A number of postoperative complications were documented including scrotal complications such as edema, hematoma, infection and necrosis.…”
Section: Surgical Diagnosesmentioning
confidence: 99%
“…A number of postoperative complications were documented including scrotal complications such as edema, hematoma, infection and necrosis. Wound infection and dehiscence were frequent complications as well (32). Postoperative outpatient attendance was poor as 298 patients were lost at the follow-ups in the postoperative sixth month, and only 17 patients attended the outpatient follow-ups for more than 2-5 years.…”
Section: Surgical Diagnosesmentioning
confidence: 99%